A SYNTACTICAL PATTERN OF 2.5 YEARS OLD BOY UTTERANCE (A CASE STUDY) - Umam, Akhmad Hairul (English Department, University of Riau Kepulauan, Batam,Indonesia, 2020)
This study aims to identify the utterances and to explore the language acquisition for 2.5 years old boy in its syntactical pattern. Â The duration of this research is four months by observing and recording the words expression pronounced by the boy. Based on the finding, this boy firmly acquires the language mostly by nature (innate ability). However, the positive environment enables him to develop the childâ€™s language fluency. Both nature and environment have important roles in the child language acquisition. It is in line with the theoretical frame work of language acquisition that in general language acquisition is shaped and influenced mainly by two factors: biological (innate ability) and environmental factors. Awhile the type of the utterances spoken by the boy aged 2.5 years old consisting of declarative 48 %, interrogative 29%, imperative 21%, and exclamation utterances 2%. In the syntacticalÂ pattern, the boy mostly speaks using the predicate utterances pattern (P), subject-predicate (S-P), then predicate-subject (P-S). The predicate (P) and subject-predicate (S-P) pattern of utterances are the most frequently spoken by boy. The boy is accustomed to and easily expresses his intentions with those two patterns that have represented a complete utterance according to what the boy intended.